1986
DOI: 10.1088/0031-8949/33/5/011
|View full text |Cite
|
Sign up to set email alerts
|

Alfvén Solitons

Abstract: The theory of MHD soliton formation parallel to the magnetic field, as described by the DNLS equation and related models, is reviewed. The known results on the physical relevance, solutions and mathematical properties of the DNLS equation, are briefly described. New results on the extension of the theory to finite beta and three space dimensions are presented. A hybrid fluid and kinetic treatment of the case of finite temperature based on the guiding center plasma model, leads to an additional nonlocal term du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
84
0

Year Published

1990
1990
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 147 publications
(85 citation statements)
references
References 37 publications
1
84
0
Order By: Relevance
“…A fully kinetic calculation was undertaken by Rogister [5] for the case of a high-beta plasma. For parallel propagation, his results counside with equations obtained later by Mjølhus and Wyller [12,6] and Spangler [13,14]. The effect of Landau damping appears in the DNLS via an additional cubic term which is an integral operator over space.…”
Section: Introductionsupporting
confidence: 68%
See 3 more Smart Citations
“…A fully kinetic calculation was undertaken by Rogister [5] for the case of a high-beta plasma. For parallel propagation, his results counside with equations obtained later by Mjølhus and Wyller [12,6] and Spangler [13,14]. The effect of Landau damping appears in the DNLS via an additional cubic term which is an integral operator over space.…”
Section: Introductionsupporting
confidence: 68%
“…We first use one-fluid MHD equations with parallel dissipation coefficients µ and χ which are constant and independent of mode frequency and wave-number. Later we replace constant χ with the integral operator representation of Hammet and Perkins [17], and obtain a modifield DNLS similar to that obtained by Mjølhus and Wyller [12,6] and Spangler [13,14]. However, our approach yields expressions for coefficients of the nonlinear terms which are much simpler than theirs and allows clear, unambiguous physical interpretation of the results.…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…For example, in space plasma, when the DNLS equation was generalized to a multi-dimensional one [27,28], it was shown that the dark solitons are not stable in presence of transverse perturbations [28].…”
mentioning
confidence: 99%